AN ANALYSIS OF THE USE WHATSAPP MEDIA IN TEACHING WRITING DESCRIPTIVE TEXT - Chrristiana Hutagaol; Mundriyah Y Pamungkas; Refi Ranto Rozak (IKIP Siliwangi, 2024)
This studied aims to found outthe students’ response and difficulties in online learned descriptive text through WhatsApp. The subject of this researched was junior high school students who were in seventh grade. The data of this research were obtained by questionnaire and one open-ended question,questionnaire was distributed through Google Form. There were 19 students filled out the form. The results showed that students had positive response to the use of Whatsapp in online learning. However, they found several obstacles, about 47% said they had no difficulties, 31% said they had difficult personal conditions, and 21% of the 19 students said it was difficult to find a good connection. In the case they did not have quota and good signal. This impacted to their understanding of the material given. Besides, some of them had a problem in using WhatsApp, it was due to the smarthphone condition. This indicates that good access and has quota is one of important to conduct the online learning. The other supportive aspect is having good smartphone or tools.